Effect Of Changes In Tax Rates, Tax Awareness, And Tax Knowledge On MSME Taxpayer Compliance at the Blora Primary Tax Service Office - Subagio, Sifa Rhodatul Jannah; Aresteria, Maya (BIMA Journal (Business, Management, & Accounting Journal), 2023)
MSME have an important role in the economy in Indonesia, this is reflected in their number which reaches 99% of all business units, and the contribution of MSMEs themselves to GDP also reaches 60.5%. Along with the increasing business development, the government also continues to issue new regulations regarding MSME taxation. One of them is the regulation regarding the change in tax rates from 1% to 0.5%. However, along with the rapid growth of MSME taxation, this is not supported by the level of compliance. Along with the continued enactment of new regulations issued by the government, this study aims to determine (1) The effect of changes in tax rates on MSME taxpayer compliance at Blora Primary Tax Service Office (2) The effect of tax awareness on MSME taxpayer compliance at Blora Primary Tax Service Office (3) The effect of tax knowledge on MSME taxpayer compliance Blora Primary Tax Service Office. The population in this study were MSME taxpayers registered at Blora Primary Tax Service Office, with the number of samples taken as many as 100 MSME taxpayers registered at the Blora Primary Tax Service Office. The data collection technique used in this research is Purposive sampling technique with data analysis techniques used are classical assumption tests and multiple linear regression analysis. The results showed that changes in tax rates and tax awareness have an influence on MSME taxpayer compliance at Blora Primary Tax Service Office, while tax knowledge has no influence on MSME taxpayer compliance at Blora Primary Tax Service Office